Mediatization and the Internet of Things - Miller James (Cultural Science)
This article offers evidence from a literature review that mediatization research has yet to engage with the internet of things (IoT). This is a major lack, given the widely recognized importance of IoT phenomena, and may be attributable to mediatization’s limited direct interest in media technology. Through an extended examination of media in cars, the article demonstrates the fertility of a mediatization approach toward what is argued to be a prototype example of the emerging IoT. The article concludes by suggesting future directions for empirical studies.